Motives for Participating in the Social Humanities Research Student Creativity Program at Sam Ratulangi University - Warouw, Desie M.D.; Himpong, Meity D.; Onsu, Reiner R. (Newinera Publisher, 2023)
The role of students in supporting creativity programs, especially social and humanities research at Sam Ratulangi University, is very important, because apart from attending lectures, they will become human resources who have academic knowledge, management skills, communication skills, but Students are also expected to have the skills and creativity to carry out research, in order to become productive, superior, competitive, adaptive, flexible, productive and competitive graduates during the industrial revolution 4.0. As well as the achievement of higher education KPI. This research uses Phenomenological Theory from Alfret Schutz, using Qualitative methods. Data Collection: Observations, Interviews, and Document Study. Research Informants: Deputy Dean for Student Affairs, Assistant Lecturers, Students Participating in Social Humanities Research. The results of the research show that the motives for participating in the Social Humanities Research Student Creativity Program at Sam Ratulangi University are: (1) Because Motive (Cause),: - Opening up the opportunity to take part in the Student Creativity Program (PKM) - Encouragement from the accompanying lecturer - As a profitable challenge to develop ideas, Creativity and Innovation Through Research - Opportunity to Work as a Team - Qualified for the National Student Science Week (PIMNAS). (2) In Order To Motive (Goal): - Graduate without a thesis - Contribution to universities and faculties - Find solutions to social phenomena that are beneficial to society. (3) Obstacles encountered: - Difficult to find accompanying lecturers - Limited time to discuss with the team and lecturers - Confused about finding phenomena and determining titles - Difficult to find friends to build a team.